Neural activations of the acquisition of conditioned sexual arousal: effects of contingency awareness and sex. - Klucken, Tim; Schweckendiek, Jan; Merz, Christian J.; Tabbert, Katharina; Walter, Bertram; Kagerer, Sabine; Vaitl, Dieter; Stark, Rudolf (The journal of sexual medicine, 2009)
INTRODUCTION: Learning processes like classical conditioning are involved in mediating sexual behavior. Yet, the neural bases underlying these processes have not been investigated so far. AIM: The aim of this study was to explore neural activations of classical conditioning of sexual arousal with respect to sex differences and contingency awareness. METHODS: In the acquisition phase, a geometric figure (CS+) was presented for 8 seconds and was followed by highly sexual arousing pictures (UCS), whereas another figure (CS-) predicted neutral pictures. Ratings and contingency awareness were assessed after the entire conditioning procedure. Forty subjects (20 females) were classified into one of four groups according to their sex and the development of contingency awareness (aware females, aware males, unaware females, and unaware males). MAIN OUTCOME MEASURES: Blood oxygen level dependent (BOLD) responses measured by functional magnetic resonance imaging (fMRI), skin conductance responses (SCRs), and subjective ratings. RESULTS: fMRI analysis showed two effects (awareness and sex) when comparing CS+ with CS-: (i) aware compared to unaware subjects showed enhanced differentiation (e.g., ventral striatum, orbitofrontal cortex, occipital cortex); and (ii) men showed increased activity compared to women in the amygdala, thalamus, and brainstem. CS+ and CS- ratings differed in aware subjects only. However, no conditioned SCRs occurred in any group. CONCLUSION: The increased activity in men is in line with theories postulating that men are generally more prone to conditioning of sexual arousal. Further, contingency awareness seems to be an important factor in appetitive learning processes, which facilitates conditioning processes.
Keywords: Amygdala/physiology; Arousal/*physiology; Awareness/physiology; Basal Ganglia/physiology; Brain Stem/physiology; Conditioning, Classical/physiology; Female; Frontal Lobe/physiology; Galvanic Skin Response; Gyrus Cinguli/physiology; Humans; Magnetic Resonance Imaging; Male; Occipital Lobe/physiology; Sex Characteristics; Sexual Behavior/*physiology; Thalamus/physiology; Young Adult

Anticipation of reward in a nonaversive differential conditioning paradigm and the brain reward system: an event-related fMRI study. - Kirsch, Peter; Schienle, Anne; Stark, Rudolf; Sammer, Gebhard; Blecker, Carlo; Walter, Bertram; Ott, Ulrich; Burkart, Jessica; Vaitl, Dieter (NeuroImage, 2003)
Findings from animal as well as human neuroimaging studies suggest that reward delivery is associated with the activation of subcortical limbic and prefrontal brain regions, including the thalamus, the striatum, the anterior cingulate and the prefrontal cortex. The aim of the present study was to explore if these reward-sensitive regions are also activated during the anticipation of reinforcers that vary with regard to their motivational value. A differential conditioning paradigm was performed, with the presentation of a rewarded reaction time task serving as the unconditioned stimulus (US). Depending on their reaction time, subjects were given (or not given) a monetary reward, or were presented with a verbal feedback consisting of being fast or slow. In a third control condition no task needed to be executed. Each of the three conditions was introduced by a different visual cue (CS). Brain activation of 27 subjects was recorded using event-related functional magnetic resonance imaging. The results showed significant activation of the substantia nigra, thalamic, striatal, and orbitofrontal brain regions as well as of the insula and the anterior cingulate during the presentation of a CS signalling a rewarded task. The anticipation of a monetary reward produced stronger activation in these regions than the anticipation of positive verbal feedback. The results are interpreted as reflecting the motivation-dependent reactivity of the brain reward system with highly motivating stimuli (monetary reward) leading to a stronger activation than those less motivating ones (verbal reward).
Keywords: *Reward; Adult; Brain/*physiology; Conditioning, Operant/*physiology; Feedback/physiology; Female; Gyrus Cinguli/physiology; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Neostriatum/physiology; Occipital Lobe/physiology; Prefrontal Cortex/physiology; Psychomotor Performance/physiology; Reaction Time